Fulfillment of Women's Constitutional Rights to Protection from Sexual Violence in University - Nisa, Siti Maymanatun; Ibrahim, Maulana Hasan (Asian Journal of Law and Humanity, 2024)
Increasing awareness of the need to protect women's constitutional rights, especially in the context of preventing and handling sexual violence in higher education, is the subject of increasingly in-depth attention. This research aims to investigate the fulfillment of women's constitutional rights in terms of protection against sexual violence in higher education environments, with a focus on the K.H. State Islamic University. Abdurrahman Wahid Pekalongan as a case study. The research method used is empirical juridical with statutory, conceptual and case approaches. Data was collected through interviews with respondents and literature study. The results of this research show that cases of sexual violence that occurred at UIN K.H. Abdurrahman Wahid Pekalongan, there were 12 cases where the victims were predominantly women. UIN K.H. Abdurrahman Wahid Pekalongan has attempted to fulfill women's constitutional rights to protection from sexual violence, but there are still several factors that are obstacles. Patriarchal culture, negative assessments of cases of sexual violence, lack of budget, lack of socialization, and intervention or threats against victims are things that need to be considered in efforts to handle sexual violence in the campus environment.